EXPLAINING NARRATIVES BATTLE BETWEEN CHINA & UNITED STATES THROUGH STAKEHOLDER ANALYSIS - Mahmud Syaltout Syahidulhaq Qudratullah; Tatok Djoko Sudiarto; Bimantoro Kushari Pramono; Febry Triantama (Jurnal Scientia, 2023)
China’s soft power is declining. Previous studies find that the United States’ narrative attack on China’s credibility is the main cause of this decline. Trade war, anti-democratic country, Human Rights violations in Xinjiang, and untransparent Covid-19 handling are prominent issues that are used by the United States to attack China. This research aims to identify stakeholders between two countries that involves in the narrative battle based on their sentiments and ability to be a key reference in particular issues related to China’s soft power. Using Social Network Analysis and appraisal theory, this research maps stakeholder positions in five quadrants: Advocate, Follower, Opponent, Blocker, and Indifferent. The key findings of this research are on stakeholders and the narratives that are founded in Advocate and Follower quadrants. Stakeholders founded in Advocate and Follower quadrants such as US scientists, NGOs, and mass media show China’s public diplomacy is running well. Different from US government stakeholders, a stakeholder in Advocate and Follower has positive sentiment about China’s Political System and economic development.